Innovation as knowledge and learning. - Taylor Rosemary (Adult Education Research Conference, 1997)
Innovative small and medium enterprises now play a vital role in the economy, but their survival often depends on being at the leading edge of their field. Without an abundance of time or money for education or training, they rely heavily on obtaining knowledge informally through a variety of channels.